Effect of long term feeding of T-2 and HT-2 toxin contaminated diet on the glutathione redox status and lipid peroxidation processes in common carp (Cyprinus carpio L.) - Balogh, Krisztián (Acta Biologica Szegediensis, 2009)
Effect of sublethal T-2 (2.45 mg kg-1 feed) and HT-2 (0.52 mg kg-1 feed) toxin treatment for 4 weeks was investigated in common carp. Two groups, a control and a T-2+HT-2 toxin treated were formed. Six carps were exterminated from each group weekly. Liver samples were taken, in which reduced glutathione concentration and glutathione-peroxidase activity were measured. Free radical formation was measured by a direct reactive oxygen metabolites test, and also malondialdehyde concentration was determined. From the first week lower feed consumption and weight gain was recorded in T-2 toxin treated group, which resulted significantly lower live weight at the end of experiment. Feeding the T-2 toxin contaminated diet caused, significantly elevated glutathione concentration and glutathione-peroxidase activity during the first week. At second week the T-2 toxin loading resulted decrease in glutathione concentration and glutathione-peroxidase activity of liver as compared to the control. Although the reactive oxygen metabolite concentration was elevated in T-2 toxin treated group during the first two weeks, no significant changes were found in the MDA concentration. The results show that the biological antioxidant system was able to eliminate the harmful peroxidative effect of T-2 toxin in common carp.